2015
DOI: 10.36793/psicumex.v5i2.282
|View full text |Cite
|
Sign up to set email alerts
|

Confiabilidad y validez de un instrumento que mide la dimensión sociopolítica de la calidad de vida

Abstract: ResumenLa calidad de vida ha sido abordada desde aproximaciones socioeconómicas que resaltan sus dimensiones de bienestar y capacidad como dos ejes preponderantes de discusión teórica y conceptual. Empero, desde una visión más psicosocial, el presente trabajo estableció la confiabilidad y validez de un instrumento que midió ocho factores indicativos de la dimensión sociopolítica de la calidad de vida. Para tal propósito, se llevó a cabo un estudio transversal con una muestra no probabilística de 245 estudiante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In the traditional standard model, the respondents reduced or amplified their responses to not be identified. However, in the local privacy model, a random response algorithm processes these data without altering their dimensions, volume, or categories to avoid inference or association of respondents to a group (34). The random response algorithm is compatible with iPhone or Google technology.…”
Section: Resultsmentioning
confidence: 99%
“…In the traditional standard model, the respondents reduced or amplified their responses to not be identified. However, in the local privacy model, a random response algorithm processes these data without altering their dimensions, volume, or categories to avoid inference or association of respondents to a group (34). The random response algorithm is compatible with iPhone or Google technology.…”
Section: Resultsmentioning
confidence: 99%
“…Carreón et al [35] showed that subjective wellbeing is the result of a climate of tasks subordinated to the climate of relationships and in cases of illness or accident, adherence to treatment increased subjective well-being by empowering the employee with respect to the organization, not only the worker evaluated positively his reintegration in the company, but also contemplated other job offers with greater rewards. In this same sense, García et al [36] demonstrated that the process of quality of life starts from the organizational culture and culminates with the reinsertion of the worker, as long as it circumscribes their expectations to the organizational culture.…”
Section: Discussionmentioning
confidence: 97%
“…However, adherence to treatment is not only a mediating variable between the organizational culture and the well-being of the worker, it also implies provisions in favor of self -care that are indicated by the frequency of medical consultations, medication intake, assistance to therapy and rehabilitation sessions [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations